Enhancing electrospun cellulose acetate nanofiber composites with polyacrylonitrile for advanced functional materials in flexible electronics - Mat Nong, Mohd Ali; Che Abdullah, Che Azurahanim; Ismail, Ismayadi; Ab Ghani, Mohd Hafizuddin; Md Yusof, Juraina (Universiti Malaya, 2024)
Carbon nanofibers produced via electrospinning are blended with polyacrylonitrile (PAN) and cellulose acetate (CA) to form a composite material. These composites have a bright future as advanced functional materials for applications in flexible electronics, energy storage, and biomedical engineering. PAN is added to enhance the mechanical properties and flexibility of electrospun cellulose acetate (CA) membranes. This addition improves CA spinnability and strengthens the resulting nanofibers. The resulting CA/PAN carbon nanofibers can serve as self-supporting electrode materials, eliminating the need for a metal current collector and non-conductive binder, while maintaining high conductivity and electrode integrity